2011
DOI: 10.1038/ejhg.2011.66
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide spatial genetic structure of angiotensin-converting enzyme gene: a new evolutionary ecological evidence for the thrifty genotype hypothesis

Abstract: As JV Neel put forward the 'thrifty genotype' hypothesis, many researches tend to support this hypothesis involved in the regulation of energy balance. However, the phrase could equally well encapsulate broader traits and the forms of thrift should be multiple. In particular, genes involved in the regulation of water and sodium balance may also be excellent candidates as thrifty genes. In the present study, we selected the ancestral D allele of angiotensin-converting enzyme (ACE) gene, a key gene involved in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 38 publications
(69 reference statements)
2
37
0
1
Order By: Relevance
“…Proponents of the thrifty gene hypothesis have examined other genes that provide support to the thrifty gene hypothesis for diabetes prevalence. The ancestral hypertension sensitive gene has been proposed by some researcher to be a thrifty gene (Li et al, 2011). Researchers have investigated the evolutionary ecology of the hyper-tension sensitive gene's (ancestral D allele of angiotensin-converting enzyme [ACE]) propensity for water and sodium retention and subsequently blood pressure regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proponents of the thrifty gene hypothesis have examined other genes that provide support to the thrifty gene hypothesis for diabetes prevalence. The ancestral hypertension sensitive gene has been proposed by some researcher to be a thrifty gene (Li et al, 2011). Researchers have investigated the evolutionary ecology of the hyper-tension sensitive gene's (ancestral D allele of angiotensin-converting enzyme [ACE]) propensity for water and sodium retention and subsequently blood pressure regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers concluded that the gene's sodium/water balance properties were directly related to the body's physiologic sweat response in the hot and arid climate of Africa. As descendants moved from the hot and arid climate of Africa the salt-sensitive D allele ACE gene became deleterious (Li et al, 2011). The thrifty gene hypothesis has also been proposed as a plausible explanation for the increased body mass index observed in Polynesian populations.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion allele was found to be associated with higher plasma ACE concentrations; that is, the average plasma ACE level of persons with the various genotypes follows the order DD>ID>II [1]. The I/D genotype distribution of ACE shows apparent variations among different ethnic populations throughout the world [8]. A number of research papers have reported a significant association between ACE I/D polymorphism and a series of diseases, including hypertension, type 2 diabetes, cardiovascular disease, kidney disease, cancer, and obesity [2][7].…”
Section: Introductionmentioning
confidence: 99%
“…Insertion/deletion (I/D) polymorphism of the angiotensin converting enzyme (ACE) gene is an important genetic marker that has been used in numerous studies [1][8]. ACE is a key enzyme of the renin-angiotensin system (RAS) and is widely distributed in human tissues, including the vascular endothelium, intestinal epithelium, kidney, lung, and testes [9], [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation